Prosecution of the President of the United States - Brown, H. Lowell. author. aut Link
XIV, 273 p. 1 illus.
Keywords: "Lowell Brown has written a compendious, even-handed, exhaustively-researched exploration of the arguments for and against the proposition that an American President can be criminally prosecuted while in office. No scholar, advocate, or citizen concerned with the scope of presidential power or the real danger of an emergent culture of executive branch impunity should be without this book.” —Frank O. Bowman, Professor of Law at the University of Missouri, USA, and author of High Crimes and Misdemeanors: A History of Impeachment for the Age of Trump (2019) This book provides a detailed look at the constitutional, historical, and political arguments concerning presidential immunity from prosecution, as well as the opinions of the Office of Legal Counsel that provided the justification for the decision not to prosecute President Trump. Focusing on those opinions, the book examines the constitutional basis of presidential immunity, both textual and historical, as reflected in the deliberations of the 1787 Convention and the ratification debates. The opinions are viewed in the context of the criminal investigations of Presidents Nixon and Clinton that gave rise to those opinions, as well as the pronouncements of the Supreme Court concerning their claims, and those of President Trump to immunity from judicial inquiry. Lastly, the book analyzes presidential immunity in light of the separation of powers, the availability of impeachment, and the discordance between presidential immunity and the rule of law. This new edition includes audiobook files at the chapter level. H. Lowell Brown is a practicing attorney specializing in white collar criminal defense and compliance, and has taught courses in white collar crime, international criminal law and procedure and jurisprudence at the University of Maine Law School, USA. He has written numerous law journal articles on issues of white collar crime and ethics, and is the author of five books, including The American Constitutional Tradition (2017) and High Crimes and Misdemeanors in Presidential Impeachment (2010).